Prevalence of anemia and associated risk factors among pregnant women in Lahore, Pakistan. Issue 6 (3rd July 2019) - Ullah, Azmat; Sohaib, Muhammad; Saeed, Farhan; Iqbal, Sanaullah
ABSTRACT: Maternal anemia is a frequent problem during pregnancy, especially in developing countries, such as Pakistan. In this context, the present study was conducted to determine factors associated with maternal anemia prevalent among women of different age groups visiting different hospitals in Lahore from February to April 2017. The current study used a cross-sectional design involving 390 pregnant women. Data related to demographic area, maternal age, gestational age/period, educational and income level, as well as socioeconomic status of all the participants were collected. Also, hemoglobin levels of the participants were obtained for assessment of maternal anemia. A total of 57.7% of participants were anemic (34.4 % mild and 23.3% moderate anemia). Bivariate analysis showed that less education ( p = 0.01), occupation as housewife ( p = 0.03), lower income ( p = 0.001), rural residence ( p = 0.028), and greater number of house members ( p = 0.04) were significantly associated with maternal anemia. Results of multivariable logistic regression showed that low income was the only significant factor independently associated with maternal anemia. These results suggest that interventions, such as the Nutrition Support Program, to improve nutritional status of pregnant women by providing free food supplements with focus on the poor and marginalized communities are recommended to prevent anemia.